Writing Groups for Healthcare Professionals in Academic Medicine - Ivana T. Croghan; Shaji Kumar; Sagar B. Dugani; Ryan T. Hurt; Laura E. Raffals; Anne A. Schletty; Darrel R. Schroeder; Shelby R. Gathje; Vijay Shah (Journal of Primary Care & Community Health, 2024)
Within the Department of Medicine (DOM) in a large tertiary academic health care facility in midwestern United States, we have developed an educational offering that incorporates an academic writing program (AWP) blending the approaches of a writing accountability work group, a writing workshop, and didactic writing courses. The purpose of this AWP was to assist healthcare professionals (HCP) with their manuscript writing skills to enhance academic productivity. We report our evolving journey and experiences with this AWP. To date, it has been offered 3 times to 25 HCP over the course of 3 years. Among those responding to a post program follow up survey (N = 11), 8 (73%) indicated that they completed the project that they were working on during the AWP and went on to publish the manuscript (N = 5) or were in the process of submission (N = 2). Some indicated they has also gone on to present posters (N = 2) or were in the process of presenting posters (N = 2) or had received grants (N = 1) or were awaiting grant notice (N = 1). A number of attendees have continued to use and share the tools presented during the AWP. Based on input from attendees and increased requests for this AWP, this educational program has been deemed a success and expansion of this program is currently underway.